Evolution of endogenous enzyme activities and virgin olive oil characteristics during Chétoui and Chemlali olive ripening. Issue 5 (16th September 2016) - Hachicha Hbaieb, Rim; Kotti, Faten; Vichi, Stefania; Gargouri, Mohamed
Abstract : The composition and biochemical characteristics of olive fruits, mainly olive enzymes system, are crucial in determining the final quality of virgin olive oil (VOO). Thus, olives endogenous olive enzyme activities were studied during Chétoui and Chemlali olive ripening. The compositional quality of the corresponding VOO was also studied. Peroxidase (POX) and β‐glucosidase activities increased during olives ripening. However, polyphenoloxidase activity decreased slowly. Moreover, the POX enzyme appears to play an essential role in determining VOO total phenol amounts, as the decrease in phenol content registered during olive ripening coincided with the increase in POX activity. A positive correlation between oil antioxidant activity and the total phenol content was established for both the olive cultivars studied. With regard to pigments, chlorophyll content was much higher than that of carotenoids in both Chétoui and Chemlali oils. Moreover, different trends in chlorophyll and carotenoid contents were observed, depending on the olive cultivar. Concerning volatile compounds, our results showed that the highest content of total C6, C5 LOX compounds, and pentene dimers was observed at a RI of approximately 3 for both cultivars. However, C6 alcohols and total C5 compounds decreased in Chétoui and Chemlali oils, respectively, during olive ripening. Practical applications: Volatile and phenolic compounds play an important role in determining VOO quality. However, these compounds were affected by numerous factors, such as, endogenous olive enzyme activities. Monitoring these enzymes activities (peroxidase, polyphenoloxidase, and β‐glucosidase) during olive fruits ripening by a simple spectrophotometric assay could be useful to establish an optimum harvesting date for each olive cultivar and their possible correlation with VOO total phenol amount. Evolution of endogenous olive enzyme activities (POX, peroxidase; PPO, polyphenoloxidase; and β‐glucosidase) during Chétoui (●) and Chemlali (○) olive ripening. Abstract : Evolution of endogenous olive enzyme activities (POX, peroxidase; PPO, polyphenoloxidase; and β‐glucosidase) during Chétoui (●) and Chemlali (○) olive ripening.